IDENTIFICATION OF GENDER DIFFERENCES IN ELEMENTARY SCHOOL STUDENTS’ METACOGNITIVE KNOWLEDGE ABOUT THE ENVIRONMENTAL CLEANLINESS - Purnama Dewi; Eddy Noviana; M. Jaya Adi Putra (Indonesian Journal of Elementary Teachers Education, 2020)
This study aims to determine students’ metacognitive knowledge about the cleanliness of the school environment in class V elementary school 130 Pekanbaru. The category of students’ metacognitive knowledge reviewed in this study is very low, low, medium, high, and very high categories. This research was conducted to 94 fifth grade students of Sekolah Dasar 130 Pekanbaru. The instrument used to collect data was a metacognitive knowledge test about the cleanliness of the school environment consisting of 12 essay questions. Data analysis used quantitative descriptive methods. The results showed that students’ metacognitive knowledge about the cleanliness of the school environment in class V elementary school 130 Pekanbaru showed a medium category with an average value of 58,8. Based on the result of the analysis, it was also found that there was a gender difference that female students were superior to male students, where the students’ metacognitive knowledge about the cleanliness of the school environment was very low and in the low category was dominated by male students.Keywords: metacognitive knowledge; cleanlines of the school environment; quantitative descriptive.